The Ironic Transhumanity of William Gibson’s The Peripheral - Esko Suoranta (Fafnir, 2016)
The article discusses transhuman futures in William Gibson’s 2014 novel The Peripheral. Through differing depictions of transhuman characters in two timelines coming into contact, Gibson presents various characters as metaphorical cyborgs. Some appear as ironic figures struggling with a capitalist system seeking to incorporate them, others follow a schizoid ethos, embracing, and sometimes embodying, the kleptocratic logic of Gibson’s worlds. Further, the novel examines the possibilities of technology to transform both individual experience and oppressive social structures. This interrogation reveals Gibson’s critical attitude toward technology alone as capable of overthrowing dystopian systems. Finally, the article interrogates the idea of mysterium tremendum et fascinans in relation to transformative technologies in the novel, in turn shedding light on Gibson’s criticism of singularity narratives. Through such an approach, the dystopian ironies of Gibson’s futures become clear: despite miraculous advancements, the dystopia remains the same for the characters inhabiting his worlds.